Simultaneous Growth of Rutile TiO2 Nanorod on FTO Plate by One-Step Hydrothermal Process for CdS Sensitized Solar Cell Applications - Ravi, Vignesh; Bojarajan, Arjun Kumar; Vaithiyanathan, Vetrivelan; Chinnadurai, Ragupathi; Kasinathan, Kaviyarasu; Gopal, Ramalingam (International Journal of Chemistry and Materials Research, 2019)
The rutile TiO2 of nanoparticles and microrods were simultaneously grown on FTO glass slide using a one-step hydrothermal process. CdS semiconducting nanocrystals were deposited on the surface of TiO2 surface using SILAR method. Moreover, the SEM micrograph studies, TiO2 nanorods were almost uniformly explored on FTO glass slide pattern. The photovoltaic performances, as-prepared semiconductor sensitized solar cells (SSSCs) were studied and the maximum efficiency of FTO/TiO2/CdS-8/ZnS-2 sample was 0.78% were confirmed by sun solar simulator, overall the solar cell efficiency was determined with an increasing pattern of CdS deposition is reported in detail.